An investigation of stimulated emission processes in thin-film molecular materials and structures - Xia, Y (2020)
Molecular semiconductor materials are highly attractive as gain media for solid state lasers and amplifiers. Devices based on thin-film structures show great potential in miniaturised, tunable and flexible lasing applications at a low cost. The ultimate aim in this context is the realisation of electrically pumped organic semiconductor lasers. One of the main challenges is understanding the relationship between material properties and stimulated-device performance, i.e. identifying generally applicable molecular structures that facilitate amplified spontaneous emission (ASE) or lasing.